2015
DOI: 10.12659/ajcr.893729
|View full text |Cite
|
Sign up to set email alerts
|

Wait!!! No Steroids for this Asthma…

Abstract: Patient: Female, 31Final Diagnosis: Hyperinfection syndrome due to Strongyloides stercoralisSymptoms: Abdominal pain • shortness of breathMedication: PrednisoneClinical Procedure: Bronchoscopy with BALSpecialty: PulmonologyObjective:Unusual clinical courseBackground:Strongyloides stercoralis (SS) is a parasite seen in certain parts of the USA and in people from other endemic areas. In these patients steroids might precipitate or exacerbate asthma. Apart from worsening of asthma, serious complications like hype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Strongyloidiasis is a cosmopolitan neglected disease, whose complications are strongly associated with alcoholism, organ transplants, HTLV-1 virus, and immunosuppression in general [ 11 14 ]. It is important to highlight that, even with early diagnostic, problems associated with the tests sensitivity may lead to false negatives, raising a need for new diagnostic methodologies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Strongyloidiasis is a cosmopolitan neglected disease, whose complications are strongly associated with alcoholism, organ transplants, HTLV-1 virus, and immunosuppression in general [ 11 14 ]. It is important to highlight that, even with early diagnostic, problems associated with the tests sensitivity may lead to false negatives, raising a need for new diagnostic methodologies.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have been published using murine models focusing in immunodiagnostic or in the host immune response, in an attempt to understand immunological aspects that are still unknown [ 4 10 ]. Immunosuppression has been correlated with the infection aggravation, mainly in cases of HTLV-1 virus coinfection, alcoholism, and corticoids use [ 11 14 ]. Understanding the parasite behavior in this particular context will allow not only the research and development of better therapeutic options but also better diagnostic methodologies that could lead to detection of lower parasite burden infections, allowing patients to be treated before their health deteriorates.…”
Section: Introductionmentioning
confidence: 99%
“…Ostera et al detected a prevalence of 4.2% among Latin American immigrants in Washington DC, USA [34]. More than half of the cases included in the literature review (Table 1) were reported in developed countries including the USA, England, France, and South Korea [1318, 20, 24]. However, all the patients were exposed to endemic areas.…”
Section: Discussionmentioning
confidence: 99%
“…2015 [23]70/MEEA, steroids, DMDM109YESYESNANAIVM, 2 daysSurvived13Alsharif et al . 2015 [24]31/FEEA, steroidsNone3831YESYESNANAIVM, 17 daysSurvived14Wang et al . 2016 [25]NA/MEEA, steroidsNone1099YESYESLarvae in duodenal mucosaNAABZ, 14 daysDied ABZ albendazole, AEC absolute eosinophil count, BAL bronchoalveolar lavage, COPD chronic obstructive pulmonary disease, DEC diethylcarbamazine, DM diabetes mellitus, EEA exposure to an endemic area, F female, IVM ivermectin, M male, NA not available, RA rheumatoid arthritis, TBZ thiabendazole…”
Section: Literature Analysismentioning
confidence: 99%
“…For instance, Alsharif et al diagnosed a woman, who lived Mexico, with hyperinfection syndrome due to Strongyloides stercoralis , most probably exacerbated by prednisone given for asthma. Steroid was discontinued and she improved with treatment [ 28 ]. Due to such effects, it has been proposed that the use of corticosteroids may be associated with the development of atherosclerosis, although until now this connection has not been clearly established [ 29 ].…”
Section: Discussionmentioning
confidence: 99%